2017
DOI: 10.1021/acs.jced.7b00118
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized-Synthetic Methodology for Solubility Determination at Elevated Temperatures with Application to Paracetamol in Pure Solvents

Abstract: This paper describes a new nonintrusive method for the determination of high-temperature solubility data. Accurate high-temperature solubility data is vital to many industrial manufacturing processes such as cooling crystallization with direct implications for yield, throughput, and solvent usage. However, the provision of such data is notably absent from published literature for many active pharmaceutical ingredients. Pressurized-synthetic methodology is presented as a new technique for determining high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The solubility of paracetamol in cyclohexane is negligible (0.0539 g/kg at 298.15 K) and was therefore suitable to use without the risk of any dissolution of paracetamol . Solubility plays an important role to interpret the mechanism of a given crystallization system which was, therefore, taken from well-established literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of paracetamol in cyclohexane is negligible (0.0539 g/kg at 298.15 K) and was therefore suitable to use without the risk of any dissolution of paracetamol . Solubility plays an important role to interpret the mechanism of a given crystallization system which was, therefore, taken from well-established literature …”
Section: Methodsmentioning
confidence: 99%
“…17 Solubility plays an important role to interpret the mechanism of a given crystallization system which was, therefore, taken from wellestablished literature. 30 The crystallization experiment was initially carried out at a small scale of 120 mL solution (paracetamol in propan-2-ol) at a low level of initial supersaturation ratio of S o = 1.0, measured in g of solute/kg of solvent, over the range of saturation temperatures, 30 to 60 °C. At each saturation temperature, the solution was crystallized at 300 and 370 rpm under a constant cooling rate of 0.1 °C/min.…”
Section: Cooling Crystallizationmentioning
confidence: 99%
“…The results presented in terms of supersaturation ratio ( S r ) have been calculated using eq , where C is the concentration of the solution measured through FTIR and C eq is the concentration at solubility which was taken from the literature …”
Section: Resultsmentioning
confidence: 99%
“…A saturated solution was prepared at 50 °C with a low level of initial supersaturation ratio of S o = 1.0, measured in g of solute/kg of solvent. A solution was prepared in accordance with solubility data which was taken from a well-established literature . The solution was crystallized at a constant cooling rate of 0.1 °C/min.…”
Section: Experimentationmentioning
confidence: 99%
“…Gibson33 reported that the effect of pressure on the solubility of a solid was significant only in very rare cases, which were concluded by the empirical and theoretical considerations Therefore, the modified Apelblat equation, the h equation and the NRTL model can also be applied to correlate the solubility data of TBBS in tert-butylamine at temperature from 318.2 K to 343.2 K34 . The fitting parameters of the models together with ARD and RMSD were listed inTable 12.…”
mentioning
confidence: 99%